A new repetitive element of the CR1 family downstream of the chicken vitellogenin gene. - van het Schip, F (1987)
We have analyzed a repetitive DNA sequence found in the 3'-flanking region of the chicken vitellogenin gene. By its sequence, the repetitive DNA has been identified as a hitherto unreported member of the chicken CR1 family of repetitive elements. The CR1 sequence displays the structural characteristics of a long terminal repeat located at the 3' end of an avian retrovirus. The CR1 element lies 2.2 kb downstream of the vitellogenin gene and 'points' away from the gene rather than toward it. In this respect, this element differs from other CR1 repeats. The CR1 element is embedded in a region showing changes in chromatin structure implying a potential role for this sequence in determining the structural state of the local chromatin.